Rethinking the relationship between plagiarism and academic integrity - Jamieson, Sandra; Howard, Rebecca (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2019)
The term academic integrity is in widespread use, and while there has been much debate about what is included under that term and how we measure and encourage integrity in an academic context, no specific definition has been codified and universally accepted. This article reviews the historical evolution of the phrase through scholarship beginning in the 1960s, its shifting definition as an ethical or moral concept, and the ways in which it is currently being used, with a focus on the logics by which textual errors came to be classified as moral lapses. This article also provides analysis of students’ textual errors as they work from sources. Based on these analyses, we advocate bringing together all cheating behaviors, including academic ghostwriting, under the umbrella of academic integrity and calling them cheating, plain and simple. At the same time, we contend that textual errors such as patchwriting and faulty citation should be removed from the moral category of academic integrity and treated as instances of bad writing to be remedied by pedagogy, not punishment.